2020
DOI: 10.12998/wjcc.v8.i14.3021
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of randomized controlled trials of colorectal cancer over the last decade

Abstract: BACKGROUND Colorectal cancer is one of the most common cancers globally. In China, its prevalence ranks fourth and fifth among females and males, respectively. Presently, treatment of rectal cancer follows a multidisciplinary comprehensive treatment approach involving surgery, radiotherapy, chemotherapy, and targeted therapy. With deepening theoretical and molecular research on colorectal cancer, randomized controlled trials (RCTs) on colorectal cancer have made significant progress. However, many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To date, there is not a bibliometric study assessing depression research and COVID-19 at the global level. In several studies in virology[ 17 - 22 ], more specifically on the COVID-19 outbreak[ 23 - 29 ], bibliometric analysis means evaluating the research output of authors, countries, journals, and institutions[ 30 , 31 ]. Capturing the relevant literature is essential and promotes the comprehension of a particular focus area's characteristics and patterns.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is not a bibliometric study assessing depression research and COVID-19 at the global level. In several studies in virology[ 17 - 22 ], more specifically on the COVID-19 outbreak[ 23 - 29 ], bibliometric analysis means evaluating the research output of authors, countries, journals, and institutions[ 30 , 31 ]. Capturing the relevant literature is essential and promotes the comprehension of a particular focus area's characteristics and patterns.…”
Section: Introductionmentioning
confidence: 99%
“…29 Similarly, in an analysis, it is observed that, though, there are research papers on breast cancer from Pakistan, with global collaboration, but improvement is warranted. 30 Regarding colorectal cancer, the contribution for the top ten RCTs and top ten institutes are from developed nations 31 . These examples, and many others in literature, show the paucity of high-quality research from Pakistan, indicating the need of a big paradigm shift in research policies at all levels.…”
Section: Discussionmentioning
confidence: 99%